Ambient temperature-related sex ratio at birth in historical urban populations: the example of the city of Poznań, 1848-1900 - Liczbińska, Grażyna; Antosik, Szymon; Brabec, Marek; Tomczyk, Arkadiusz M (Scientific reports, 2024)
This study examines whether exposure to ambient temperature in nineteenth-century urban space affected the ratio of boys to girls at birth. Furthermore, we investigate the details of temperature effects timing upon sex ratio at birth. The research included 66,009 individual births, aggregated in subsequent months of births for the years 1847-1900, i.e. 33,922 boys and 32,087 girls. The statistical modelling of the probability of a girl being born is based on logistic GAM with penalized splines and automatically selected complexity. Our research emphasizes the significant effect of temperature in the year of conception: the higher the temperature was, the smaller probability of a girl being born was observed. There were also several significant temperature lags before conception and during pregnancy. Our findings indicate that in the past, ambient temperature, similar to psychological stress, hunger, malnutrition, and social and economic factors, influenced the viability of a foetus. Research on the effects of climate on the sex ratio in historical populations may allow for a better understanding of the relationship between environmental factors and reproduction, especially concerning historical populations since due to some cultural limitations, they were more prone to stronger environmental stressors than currently.
Keywords: Female; Cities; History, 20th Century; Urban Population; novorozenec; teplota; ženské pohlaví; velkoměsta; lidé; porod; Infant, Newborn; Sex Ratio; těhotenství; Parturition; dějiny 20. století; Temperature; Male; poměr pohlaví; městské obyvatelstvo; History, 19th Century; mužské pohlaví; dějiny 19. století; Pregnancy; Humans